EDUCATIONAL TECHNOLOGIES FOR TEACHING RUSSIAN IN NON-PHILOLOGICAL UNIVERSITIES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article provides information on the educational technologies used in the process of teaching Russian in non-philological higher educational institutions. In order to improve the effectiveness of learning Russian, modern pedagogical approaches are considered, such as multimedia tools, online platforms, and methods of group and team work. It also notes that such technologies serve to make the learning process for students more interactive and interesting, as well as providing opportunities for the practical application of language skills.